Evaluation of Factors Affecting the Performance of Fiber-Reinforced Subgrade Soil Characteristics Under Cyclic Loading - Frank I. Aneke; Shadi Hanandeh; Denis Kalumba (Civil Engineering Journal, 2023)
This study is focused on evaluating the factors affecting the performance of fiber-reinforced subgrade under cyclic loading. To achieve the objectives of this study, a series of dynamic triaxial (DT) tests was performed, and the following parameters, such as resilient modulus (MR), number of loading cycles (N), cyclic stress (CS), resilient strain (RS), and stress-strain hysteresis response of both the reinforced and unreinforced subgrades were evaluated. Subsequently, a series of scanning electron microscope (SEM) tests was conducted to track the fiber-soil interfacial bonding after the completion of DT test. The results indicated that N and CS triggered an appreciable decrease in MR with significantly high RS deformation for the unreinforced subgrade. However, reversed responses were noted upon the inclusion of sisal fiber due to fiber-soil adhesion and a high ductility response was portrayed by the reinforced subgrades. A reversed response was significant upon 0.25% and 0.5% fiber inclusion, beyond which the CS resistance slightly decreased. The stress-strain hysteresis loop was observed to increase as the axial strain increased proportionally with an increase in fiber contents, thus causing a significant increase in energy absorption in specimens. The SEM micrograph showed tightly knitted fiber-soil adhesion after the DT test. This study indicated that the reinforced subgrade sustained the CS, N, and improved energy absorption capacity, and MRupon fiber inclusion.Â Doi: 10.28991/CEJ-2023-09-08-015 Full Text: PDF